Comparison of the Duration and Quality of Epidural Analgesia between Plain Bupivacaine alone and Plain Bupivacaine with Tramadol in Lower Limb Orthopaedic Surgeries - Sambo YT; Adamu SA; Mahdi BM; Esin A; Nuhu AM (Ntec Specialist, 2020)
Background: This study was aimed at comparing the duration and quality of epidural analgesia between plain bupivacaine alone with plain bupivacaine and tramadol in lower limb orthopaedic surgeries. Method: This was a prospective randomized double blinded control study involving 74 ASA I and II patients scheduled for elective lower limb orthopaedic surgeries. Group A (n=37) received 19mls of 0.5% epidural plain bupivacaine with 1 ml of water for injection, while group B received 19mls of 0.5% epidural plain bupivacaine with 1ml (50mg) of preservative free tramadol. The duration of analgesia was from the time of epidural block to the time of rescue analgesia. While, the quality of block was measured with Visual Analogue Scale (VAS) and Bromage scale. Results: The study ages were between 16-60years,consisting of 22(60%) male and 15(40%) female in group A, while in group B 20 (54%) were male and 17(46%) female. It showed the mean duration of analgesia were 189.05±21.92min and 254.19±32.78min in group A and B respectively with p less than 0.01.The intra-operative VAS scores between the two groups did not show any significant difference between study groups (P greater than 0.05).The differences of grades of motor block and maximum sensory block height were not statistically significant (P=0.26) among the study groups. Conclusion: The addition of 50mg (1ml) of tramadol to plain bupivacaine epidurally prolonged the duration of analgesia and improved the quality of analgesia when compared to the use of bupivacaine alone